Pengaruh Syukur Terhadap Kebahagiaan pada Remaja Kelas 8 di SMPN 2 Payakumbuh - Rafly Rafly; Erfi Amanda; Alifia Putri Fadilah Sati; Ananda Sri Rahayu; Anisa Resa Savitri; Imelda Evani; Sakinatun Hasanah; Syerli Akhla Rosa; Ulfa Dwina (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Gratitude is an attitude that is highly emphasized and appreciated. An attitude of gratitude means recognizing ang appreciating all the blessings given by God. Teenagers who are able to be grateful for their lives will have an impact on their happiness and peace of mind. The sample in this study was 65 junior high school studendts. The aim of this research is to determine the effect of gratitude on happiness in adolescents. This research uses a quantitative approach with simple regression test aanalysis using SPPS 26.00 with data collection tools in the form of questionnaires for the gratitude scale. From the results of research data analysis, is shows that there is an influence of gratitude on happiness in teenagers of 16.9%, which is in the medion category, which means that the higher the feeling of gratitude, the more happiness will increase. So it can be concluded thatther is an influence of gratitude on happiness in teenagers.